2022
DOI: 10.1039/d2gc02075k
|View full text |Cite
|
Sign up to set email alerts
|

Choline chloride–ethylene glycol based deep-eutectic solvents as lixiviants for cobalt recovery from lithium-ion battery cathode materials: are these solvents really green in high-temperature processes?

Abstract: The thermal decomposition of the choline chloride–ethylene glycol (ChCl : EG) deep-eutectic solvent (DES) is studied during the leaching of lithium cobalt oxide (LiCoO2) at 180 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 64 publications
(126 reference statements)
3
39
0
1
Order By: Relevance
“…This can be attributed to the Cl − attack on the TM center, as has been observed in other ChClbased DES systems. 23 The UV spectra of the reaction mixture comprising DES-3 and NMC/NCA at 180 °C are recorded at As expected, in both cases, we observe the increase in the intensity of the absorbance peaks with time. The peaks at 614 nm can be attributed to octahedral cobalt complexes that may contain different ligands in their coordination sphere including chloride.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…This can be attributed to the Cl − attack on the TM center, as has been observed in other ChClbased DES systems. 23 The UV spectra of the reaction mixture comprising DES-3 and NMC/NCA at 180 °C are recorded at As expected, in both cases, we observe the increase in the intensity of the absorbance peaks with time. The peaks at 614 nm can be attributed to octahedral cobalt complexes that may contain different ligands in their coordination sphere including chloride.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…Thus, cobalt(III) could be reduced by water evolving during the dissolution reaction. Also, the formation of chlorine was reported upon the dissolution of lithium‐ion battery cathode materials in different chloride‐containing DESs, indicating chloride oxidation by cobalt(III) [22,26,27,35,36] . Meng, Guo et al.…”
Section: Resultsmentioning
confidence: 99%
“…The precipitates are suitable reagents for the production of new lithium‐ion battery cathodes [23,27,33] . Although several investigations show, that the DES can be reused for up to five times, [29,31,35] other publications raise considerable doubts regarding their stability [20,21,27,36] . For example, in DESs consisting of a carboxylic acid and an alcohol, up to 35 % of both components appear to be present in an esterified form even at room temperature [37] .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the green character of the DES is highlighted in this application [32,35,88]. However, recent research in Binnemans' group has shown that this DES is not thermally stable at such elevated temperatures and that even toxic decomposition products, such as trimethylamine or 2-chloroethanol, are formed [89].…”
Section: Limited Chemical Stabilitymentioning
confidence: 99%